Lion of the desert - Moustapha Akkad; Falcon International; Trancas International Films; PT Merak Cipta Indo Kreasi ([s.l.] : Trancas International Films ; Indonesia : PT Merak Cipta Indo Kreasi [distributor], 1991)
In the war waged by Bedouin patriots to combat Benito Mussolini's Italian colonization in Libya, Omar Mukhtar, the Bedouin resistance guerrilla leader, has committed himself to a war that cannot be won in his lifetime
Title from title screen
Subtitle in Indonesian
Film editor, John Shirley ; photographed by Jack Hildyard B.S.C ; screenplay by H.A.L. Craig ; music composed and conducted by Maurice Jarre
Cast: Anthony Quin, Oliver Reed, Irene Papas, Raf Vallone, Gastone Moschin, Andrew Keir, Sky Dumont, Robert Brown, Takis Emmanuel, Rod Steiger and John Gielgud
Keywords: Guerrilla warfare -- Libya -- Drama; Bedouins -- Libya -- Drama; Italy -- Colonies -- Libya -- Drama